2012
DOI: 10.1266/ggs.87.357
|View full text |Cite
|
Sign up to set email alerts
|

A wheat homologue of <i>PHYTOCLOCK 1</i> is a candidate gene conferring the early heading phenotype to einkorn wheat

Abstract: An X-ray mutant showing an early flowering phenotype has been identified in einkorn wheat (Triticum monococcum L.), for which a major QTL for heading time was previously mapped in the telomeric region on the long arm of chromosome 3A. Recent advances in Triticeae genomics revealed that the gene order in this region is highly conserved between wheat and barley. Thus, we adopted a hypothetical gene order in barley, the so-called GenomeZipper, to develop DNA markers for fine mapping the target gene in wheat. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
73
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 59 publications
10
73
0
1
Order By: Relevance
“…In terms of sequence conservation, we observed that the Eps-3A m locus in einkorn wheat had higher resemblance to the syntenic barley sequence than to that of bread wheat ( Figure 2A and Table S2). During our genetic characterization of Eps-3A m , we noted that two adjacent marker loci, TmLUX (PAV_261_262) and TmPUMILIO (PAV_295_296), were scored as null alleles in KT3-5 (Figure 2A), suggesting a putative deletion of both genes in agreement with previous findings (Mizuno et al 2012). DNA gel blot analysis confirmed this result ( Figure S2).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…In terms of sequence conservation, we observed that the Eps-3A m locus in einkorn wheat had higher resemblance to the syntenic barley sequence than to that of bread wheat ( Figure 2A and Table S2). During our genetic characterization of Eps-3A m , we noted that two adjacent marker loci, TmLUX (PAV_261_262) and TmPUMILIO (PAV_295_296), were scored as null alleles in KT3-5 (Figure 2A), suggesting a putative deletion of both genes in agreement with previous findings (Mizuno et al 2012). DNA gel blot analysis confirmed this result ( Figure S2).…”
supporting
confidence: 90%
“…Moreover, recent analysis of eam8 (HvELF3) and eam10 (HvLUX1) mutants showed misexpression of circadian clock gene-related transcripts (Faure et al 2012; Campoli et al 2013), which was in line with previous findings in Arabidopsis (Hicks et al 2001). So far, cereal PCL1/LUX was proposed as a candidate conferring early flowering in eam10 and KT3-5 mutants (Mizuno et al 2012; Campoli et al 2013). Authors have concluded that the mechanism of the PCL1/LUX protein action is similar in both einkorn wheat and barley; it represses expression of Vrn3/FT through the negative regulation of Ppd-1/Ppd-H1, thus delaying flowering.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, in both crop groups, mutations in ELF3 genes have been shown to contribute to the expansion in range of species through alteration of photoperiod responsiveness and the associated impact on yield (Faure et al, 2012;Matsubara et al, 2012;Weller et al, 2012;Zakhrabekova et al, 2012;Alvarez et al, 2016;Lu et al, 2017). In crop species, a role for ELF4 function has been clearly established only in the legume species pea (Pisum sativum; Liew et al, 2009), but mutations in LUX orthologs have also been shown to cause early flowering and impaired photoperiod response in pea and in the cereals einkorn wheat (Triticum aestivum) and barley (Hordeum vulgare; Mizuno et al, 2012;Campoli et al, 2013;Liew et al, 2014), suggesting that the EC genes are likely to be intimately linked to the photoperiod response mechanism in both crop groups.…”
mentioning
confidence: 99%